Green Supply Chain Coordination During the COVID-19 Pandemic Based on Consignment Contract - Wang, Yi; Reivan Ortiz, Geovanny Genaro; Dextre-Martinez, William; Zhang, Liandi (Frontiers in Environmental Science, 2022)
COVID-19 has further strengthened consumers’ online consumption habits and brought a new boom in which enterprises can use online transactions and green products to avoid risk and gain profits in the pandemic. A green supply chain model is established containing one e-commerce platform and one manufacturer. The Nash bargaining contract and Rubinstein bargaining contract are applied to mitigate conflicts of profits in the model. From the coordination analysis, we show that both Nash and Rubinstein bargaining contracts can achieve coordination and mitigate conflict of profits through the adjustment of platform usage rates. According to each member’s bargaining power and patience, the optimal platform usage rate is determined, the supply chain profits of both sides are allocated, the green production’s research and development are promoted, and a win-win situation is realized. Specifically, in the Nash bargaining contract, the excess profit of each member depends on their bargaining power. The stronger the bargaining power, the more excess profits will go to the e-commerce platform, and the less excess profits will go to the manufacturer. In the Rubinstein bargaining contract, the excess profit of each member depends on the lowest profit bound and bargaining patience. The higher the manufacturer’s (or e-commerce platform’s) patience, the higher his profit. When the patience of both is high (or low), the e-commerce platform (or the manufacturer) plays a leading role and obtains more profits.